Profesyonel basketbolcuların mental dayanıklılık ve başarı motivasyonlarının araştırılması - Avci, Muhammet Ali (Fırat Üniveristesi, 2026)
Bu araştırmada öncelikle Türkiye Basketbol Ligi ve Türkiye Kadınlar Basketbol Ligi'nde aktif oynayan sporcuların görüşleri doğrultusunda sporda mental dayanıklılıkları ile başarı motivasyonları arasındaki ilişkilerin belirlenmesi amaçlanmıştır. Bu araştırmada nicel araştırma yöntemlerinden ilişkisel tarama yöntemi kullanılmıştır. Araştırmanın evrenini Türkiye Kadınlar Basketbol Ligi ve Türkiye Basketbol Ligi'nde 2024-2025 yılında oynayan 446 sporcu oluştururken, örneklemini ise yapılan güç analizi sonucunda 150 kadın 150 erkek olmak üzere 300 sporcu oluşturmaktadır. Araştırmada kullanılan veri toplama aracı üç bölümden oluşmaktadır. Birinci bölümde araştırmacı tarafından hazırlanan, katılımcıların bireysel ve demografik verilerini ortaya koyacak olan kişisel bilgi formu; ikinci bölümde "Sporda Mental Dayanıklılık Ölçeği", üçüncü bölümde "Spora Özgü Başarı Motivasyonu Ölçeği (SÖBMÖ)" Ölçeği kullanılmıştır. Verilerin yüzde ve frekans değerleri belirlenip, ikili karşılaştırmalarda t testi ve çoklu karşılaştırmalarda anova testleri yapılmıştır. İki ölçek arasındaki ilişki için "Pearson Korelasyon" testi ve ölçekler arası etki için ise "Linear Regresyon" testlerinin sonuçlarına bakılmıştır. Sonuç olarak porfesyonel basketbol oynayan sporcuların mental dayanıklılık ortalama puanları ortalamanın altında, başarı motivasyon düzeyleri ortalamanın üstünde, cinsiyetlerine baktığımızda sporcuların mental dayanıklılıklarında kadınlarda güven erkeklerde kontrolün, 17-21 yaşlarında güven, 27 yaş ve üzeri olanlarda kontrol, kaçyıldır profesyonel basketbol oynuyorsunuzda, 0-5 yıl arasında oynayanlarda güven 16 yıl ve üzeri oynayanlarda bağlılık, kontrol ve genel mental dayanıklılığın, gelir durumunda, 0-50000 ₺ aylık geliri olanlarda güven, 100001 ₺ ve üzeri aylık geliri olanlarda kontrolün, başarı motivasyon düzeylerine baktığımızda 27 yaş ve üzeri yaşlarda, 16 yıl ve üzeri profesyonel basketbol oynayanlarda, 100001 ₺ ve üzeri aylık gelire sahip olanlarda ve lisans mezunu sporcularda güç gösterme güdüsü, daha fazla olduğu, mental dayanıklılık ve başarı motivasyonu toplam puanları arasında anlamlı bir ilişki olduğu ve düşük düzeyde bir etki olduğu tespit edilmiştir. Anahtar Kelimeler: Mental Dayanıklılık, Başarı Motivasyonu, Basketbol, Sporcu

This study primarily aims to determine the relationship between mental toughness and achievement motivation in sport, based on the perspectives of athletes actively competing in the Turkish Basketball League and the Turkish Women's Basketball League. In this study, the relational screening model, one of the quantitative research methods, was employed. The population of the study consisted of 446 athletes who competed in the Turkish Women's Basketball League and the Turkish Basketball League during the 2024–2025 season, while the sample comprised 300 athletes (150 female and 150 male), determined through power analysis. The data collection instrument used in the study consisted of three sections. The first section included a personal information form prepared by the researcher to obtain participants' individual and demographic characteristics; the second section included the 'Mental Toughness in Sports Scale'; and the third section included the 'Sport-Specific Achievement Motivation Scale (SSAMS)'. Percentage and frequency values of the data were calculated, and independent samples t-tests were conducted for pairwise comparisons, while ANOVA tests were used for multiple comparisons. The 'Pearson Correlation' test was applied to examine the relationship between the two scales, and 'Linear Regression' analysis was conducted to determine the effect between the scales. In conclusion, the mean mental toughness scores of professional basketball players were found to be below average, whereas their achievement motivation levels were above average. When examined by gender, the confidence dimension of mental toughness was higher in female athletes, while the control dimension was higher in male athletes. In terms of age, confidence was more prominent among athletes aged 17–21, whereas control was higher among those aged 27 and above. Regarding years of professional experience, confidence was higher in athletes with 0–5 years of experience, while commitment, control, and overall mental toughness were higher in those with 16 years or more experience. Concerning income level, confidence was higher among athletes with a monthly income of 0–50,000 ₺, whereas control was higher among those earning 100,001 ₺ and above. In terms of achievement motivation, the motive for power demonstration was found to be higher among athletes aged 27 and above, those with 16 years or more professional experience, those earning 100,001 ₺ or more monthly, and those holding a bachelor's degree. Additionally, a significant relationship was identified between total mental toughness and achievement motivation scores, with a low level of effect. Keywords: Mental Toughness, Achievement Motivation, Basketball, Athlete
An investigation of the mental toughness and achievement motivation of professional basketball players
Keywords: Spor